Perubahan kimiawi dan mikrobiologis selama fermentasi bekasam ikan nila menggunakan starter tunggal dan campuran: Change of chemical and microbiological during the fermentation of bekasam nile tilapia fish using single and mixed starters - Desniar, Desniar; Setyaningsih, Iriani; Fransiska, Ike Marta (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2023)
Bekasam is a fermented fish product that tastes sour. Bekasams commonly employ freshwater fish, carbohydrate sources, and salt, which are left to ferment spontaneously for a period of 5-10 days. The quality of the bekasam produced was not uniform. This study aimed to investigate the microbiological and chemical properties of bekasam during the fermentation process using a single and mixed starter, and to identify the optimal treatment for the selected starter in terms of its chemical composition and sodium chloride content. The addition of 7.5% (weight-to-weight) salt and 25% (weight-to-weight) dry rice to the prepared Nile tilapia fish was followed by sterilization at 100 °C for 30 min.The sterilized fish mixture was subjected to treatments involving the incorporation of a single starter culture containing Lactobacillus plantarum SK (5) at a concentration of 10% (v/b), as well as a mixed starter culture consisting of L. plantarum SK (5) and Pediococcus pentosaceus BP (20) at a concentration of 10% (v/w). Undertaking the fermentation of Bekasam was fermented for an interval of 8 days every 2 days, encompassing the quantification of total Lactic Acid Bacteria (LAB), pH, and Total Acid Titratable (TAT). The incorporation of single and mixed starters during fermentation resulted in consistent microbiological and chemical characteristics, characterized by an increase in the overall count of LAB and TAT, accompanied by a decrease in pH. The incorporation of a mixed starter resulted in a higher overall concentration of LAB and TAT, as well as a more rapid decrease in pH, when compared with the use of a single starter. The chosen treatment method involved the incorporation of a mixed starter possessing certain characteristics, including a moisture content of 66.56%, ash content of 5.92%, protein content of 23.06%, fat content of 3.96%, and sodium chloride content of 2.57%. Both L. plantarum SK(5) and P. pentosaceus BP(20) were deemed suitable for use as starters in bekasam fermentation